2012
DOI: 10.1111/j.1460-6984.2012.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a manualized communication intervention for school‐aged children with pragmatic and social communication needs in a randomized controlled trial: the Social Communication Intervention Project

Abstract: Predetermining theoretical background, structure, and content in a treatment manual contributed towards the quality and reliability of intervention within the context of an RCT. The implementation of SCIP intervention in a broader clinical context is discussed with reference to staff expertise, the therapeutic process and the essential ingredients of social communication intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…These components of intervention were found to be among the most frequently used in SCIP intervention (Adams et al . ) and it is notable that parent and teacher perceptions of effectiveness converge well with quantitative findings (Adams et al . ).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…These components of intervention were found to be among the most frequently used in SCIP intervention (Adams et al . ) and it is notable that parent and teacher perceptions of effectiveness converge well with quantitative findings (Adams et al . ).…”
Section: Discussionsupporting
confidence: 67%
“…In the SCIP project, a randomized controlled design was used to evaluate the effectiveness of an intensive manualized speech and language therapy intervention for CwPLI. Results indicated an intervention effect on blind and parent/teacher-reported communication outcomes, but not language test scores (Adams et al 2012a(Adams et al , 2012b.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The authors are the authors of the SCIP Manual (2015), a revised version of the research manual reported in the SCIP trial (Adams et al . , ).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The trial intervention was the social communication intervention programme (SCIP), a manualized treatment containing instructions and resources for the delivery of SLT for children with SPCD by a skilled practitioner or trained therapy assistant (ThA) (Adams et al . , ). The SCIP intervention manual contains three main components: language processing, pragmatics, and social understanding and social interpretation, and includes therapy directed at improving the child's metacognitive and meta‐pragmatic skills (Adams and Gaile ).…”
Section: Introductionmentioning
confidence: 99%